EVOCAÇÃO POÉTICA : O velar e o desvelar da obra pictórica Menino morto de Cândido Portinari à luz das concepções de Paul Tillich e de Martin Heidegger sobre as artes - Silva, Antonio Almeida Rodrigues da (2008)
Art has been always a great mystery to human beings. Its polissemic characteristic challenges us to think it as something always opened. That s to say, as something that allows people to experience art in diverse manners. By choosing de paint of Cândido Portinari, titled Menino morto (Dead boy), we pretend to show that the meeting with a work of art is forcefully actual, alive, surprising and extraordinary Rather than a mere object of pleasure, it helps human beings to unveil original experiences by opening an array of meanings so that they could fine significance to their own being. In order to go on with this investigation, this thesis focuses on studies done by the theologian Paul Tillich and the philosofer Martin Heidegger regarding to art. According to Tillich, in a work of art, we must seek what is hidden by the unapparent, because is there that its substance lies. Thus, in art, as in any cultural expression, no matter how secular it could seems, an ultimate concern is always expressed. According to Heidegger, art is a source through which truth is revealed. However, this revelation bears itself the concealment of its same truth, for both, truth and non-truth simultaneously take place in Art. Therefore, in the light of the studies done by these two authors, we attempt to undress the Dead boy . (AU)